EKSISTENSI EKSISTENSI KOMPILASI HUKUM ISLAM DI INDONESIA SETELAH DI UNDANGKANNYA UU NO 16 TAHUN 2019 TENTANG PERKAWINAN: EKSISTENSI KOMPILASI HUKUM ISLAM DI INDONESIA SETELAH DI UNDANGKANNYA UU NO 16 TAHUN 2019 TENTANG PERKAWINAN - Ana Laela Fatikhatul Choiriyah; Inayatul Anisah (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
The age of adulthood for marriage has always been a polemic both in terms of cultural factors and even the rules that govern it, the age of adulthood for marriage has long been regulated both in the Compilation of Islamic Law and Law No. 1 of 1974, over time the rules regarding the age limit for marriage have always been in the spotlight of academics so that Seeing these conditions, in 2019 Jokowi Dodo passed the Marriage Law, namely Law number 16 of 2019, seeing this condition it is known that the KHI is a reference for the Religious Court Judge but the KHI does not follow any changes to the Law which is the reference for the Religious Courts , so that with this background the author is interested in writing about the existence of a compilation of Islamic law in Indonesia after the enactment of Law No. 16 of 2019 concerning marriage using a normative juridical research methodology and a statutory approach. Keywords: Adult age, Marriage, KHI